A novel model‐driven approach for seamless integration. (15th September 2016) - Mustacoglu, Ahmet F.
Summary: This research mentions integration problems and describes a novel model‐driven approach that intend to reach a higher degree of interoperability among different software development tools coming from different technological spaces (TSs) by representing data of tools through the models. The proposed concept introduce a way to integrate various software related tools and aim to provide a modular syntax for tool integration that leverage the collaboration of different tools. In this work, the proposed approach has been tested through a case–study by demonstrating a single aspect of the model‐driven tool integration because the model‐driven tool integration has a wide scope and it is difficult to show all aspects of it in one research. It is proved that the model‐driven tool integration is possible based on the proposed concept between different TSs, and the formulation of the proposed approach is provided. As the results indicate, the proposed system integrates selected software‐related tools coming from different TSs and enables them to use each other's capabilities. This work paves the way to contribute for the standardization efforts of the model‐driven tool integration. Finally, further research opportunities are provided. Copyright © 2016 John Wiley & Sons, Ltd.